Targeting acid ceramidase to improve the radiosensitivity of rectal cancer - Clifford, R; Govindarajah, N; Bowden, D; Sutton, P; Glenn, M; Darvish-Damavandi, M; Buczacki, S; McDermott, U; Szulc, Z; Ogretmen, B; Parsons, J; Vimalachandran, D (MDPI, 2020)
Previous work utilizing proteomic and immunohistochemical analyses has identified that high levels of acid ceramidase (AC) expression confers a poorer response to neoadjuvant treatment in locally advanced rectal cancer. We aimed to assess the radiosensitising effect of biological and pharmacological manipulation of AC and elucidate the underlying mechanism. AC manipulation in three colorectal cancer cell lines (HT29, HCT116 and LIM1215) was achieved using siRNA and plasmid overexpression. Carmofur and a novel small molecular inhibitor (LCL521) were used as pharmacological AC inhibitors. Using clonogenic assays, we demonstrate that an siRNA knockdown of AC enhanced X-ray radiosensitivity across all colorectal cancer cell lines compared to a non-targeting control siRNA, and conversely, AC protein overexpression increased radioresistance. Using CRISPR gene editing, we also generated AC knockout HCT116 cells that were significantly more radiosensitive compared to AC-expressing cells. Similarly, two patient-derived organoid models containing relatively low AC expression were found to be comparatively more radiosensitive than three other models containing higher levels of AC. Additionally, AC inhibition using carmofur and LCL521 in three colorectal cancer cell lines increased cellular radiosensitivity. Decreased AC protein led to significant poly-ADP ribose polymerase-1 (PARP-1) cleavage and apoptosis post-irradiation, which was shown to be executed through a p53-dependent process. Our study demonstrates that expression of AC within colorectal cancer cell lines modulates the cellular response to radiation, and particularly that AC inhibition leads to significantly enhanced radiosensitivity through an elevation in apoptosis. This work further solidifies AC as a target for improving radiotherapy treatment of locally advanced rectal cancer. View Full-Text